Aquaculture relevant stressors and their impacts on skin and wound healing in post-smolt Atlantic salmon (Salmo salar L.) - Sveen, Lene Rydal (Aquaculture, 2018)
The work described in this thesis focuses on the response mechanisms in the skin of post-smolt Atlantic salmon (Salmo salar L.) under the following challenging conditions: i. The effect of high biomass and low specific water flow on skin integrity (paper I) ii. The effect of high biomass followed by acute challenge test on mucin transcription in skin (paper II) iii. General wound healing mechanisms in Atlantic salmon skin (paper III) and the effect of high biomass on wound healing (paper IV) iv. The effect of handling stress on mucin transcription (paper II) High biomass is predicted to provide greater profitability in the production of fish in closed systems. Similarly, low water flow can reduce costs associated with water treatment and water supply. In paper I, these hypotheses were challenged. Five fish densities (25, 50, 75, 100 and 125 kg/m3) and four levels of specific water flow (0.2, 0.3, 0.4 and 0.5 l /kg fish/min) were established to detect effects on salmon skin. After eight weeks, both high biomass (≥ 100 kg/m3) and low specific water flow, (0.2-0.3 l /kg/min) led to activated stress and immune responses in the skin of post-smolt, including increased transcription of mucin-like genes. The main constituency of the mucus layer are big gel-forming proteins called mucins. In paper II, seven gel-forming mucins, including two mucin2 and five mucin5 variants, were identified based on a computational pipeline consisting of annotation, transcription, domain structure and phylogenetic analysis. Mucin2 was predominantly expressed in the intestine, while the mucin5 family was expressed in many organs, including skin and gills. In order to investigate transcriptional regulation of mucins during stress conditions, two controlled experiments were conducted. In the first experiment, handling stress induced mucin transcription in the gill, while transcription decreased in the skin and intestine. In the second experiment, long term intensive rearing conditions interrupted by additional acute challenge test led to ...